CVAE-ADS: A Deep Learning Framework for Traffic Accident Detection and Video Summarization - Ankita Chauhan; Sudhir Vegad (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA, 2026)
Since it is a manual process of monitoring to identify accidents, it is becoming more and more difficult and results in human error, because of the rapid increase in road traffic and surveillance video. This underscores the urgent need for robust, automated systems capable of identifying accidents, as well as the burden of summarizing long videos. In order to address this issue, we propose CVAE-ADS, which is an unsupervised Approach that not only detects anomalies but also summarizes keyframes of a video to monitor traffic. This method operates in two phases. The stage of detecting Abnormalities intraffic video is performed using a Convolutional Variational Autoencoder, which operates on normal frames and identifies anomalies based on reconstruction errors. The second stage is the clustering of the perceived anomalous frames in the latent space, followed by the selection of representative keyframes to form a summary video. We tested the method with two benchmark datasets, namely, the IITH Accident Dataset and a subset of UCF-Crime. The findings have shown that the proposed approach had great accuracy of accident detection and AUC of 90.61 and 87.95 on IITH and UCF-Crime respectively and low rebuilding error and Equal Error Rates. To summarize, the method achieves substantial frame reduction and produces high visual quality with a wide variety of keyframes. It is able to measure up to 85 reduction rates with coverage of 92.5 on the IITH dataset and 80 reduction rates with coverage of 90 on an Accident subset of the UCF-Crime Dataset. CVAE-ADS offers a lightweight version of constant traffic monitoring, which utilizes limited organizational capital to categorize coincidences in real-time and recapitulate video footage of the accidents